Patient Perception and Cost-Effectiveness of a Patient Navigation Program to Improve Breast Cancer Screening for Hispanic Women - Denise A. Hern?ndez; Jos? A. Pag?n (Mary Ann Liebert, 2019)
Purpose: Hispanic women are less likely to be screened for breast cancer than non-Hispanic women, which contributes to the disproportionate prevalence of advanced-stage breast cancer in this population group. Patient navigation may be a promising approach to help women overcome the complexity of accessing multiple health care services related to breast cancer screening and treatment. The goal of this study is to assess patient perception and cost-effectiveness of a multilevel, community-based patient navigation program to improve breast cancer screening among Hispanic women in South Texas. Methods: We used mixed methods?including focus groups of program participants and a microsimulation model of breast cancer?to evaluate the effectiveness and cost-effectiveness of the program on the target population. Program data from 2013 to 2016 were collected and used to conduct the analyses. Results: Focus groups showed that the patient navigation program improved patient knowledge, attitudes, and behaviors regarding breast health and increased the mammography screening rate from 60% to 80%. Cost-effectiveness analysis showed that the program could increase life expectancy by 0.71 years and yield an incremental cost-effectiveness ratio of $3120 per quality-adjusted life year compared to no intervention. Conclusion: The 3-year multilevel, community-based patient navigation program effectively increased mammography screening uptake and adherence and improved knowledge and behaviors on breast health among program participants. Future research is needed to translate and disseminate the program to other socioeconomic and demographic groups to test its robustness and design.